Strengthening Courtroom Integrity in Indonesia: Addressing Technological and Security Challenges Through Global Best Practice - Sophia, Sally; Zahra, Salma; Azizan, Akmal; Perai, Nurajam (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
Maintaining order in the courtroom is essential for ensuring fair and efficient judicial proceedings. However, Indonesian courts face increasing challenges in managing courtroom decorum due to evolving disruptive behaviors driven by technological advancements and societal changes under the 4th Industrial Revolution. This research examines the current state of courtroom management in Indonesia, identifying gaps such as unauthorized electronic recordings, inadequate systems for remote trial decorum, and insufficient courtroom security measures. Using a literature-methods approach, the study analyzes incident reports, judicial practices, and international best practices from countries like Germany, Japan, and Canada. Findings reveal significant weaknesses in the regulation of technology use, courtroom security frameworks, and the public perception of traditional practices. The research concludes that Indonesia's judiciary must adopt forward-thinking strategies to enhance courtroom management and public trust. Key recommendations for the Supreme Court include regulating electronic device usage, establishing a court police system, introducing summary procedures for in-court offenses, and revising the